2017
DOI: 10.1007/s00213-017-4599-4
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and cross-tolerance to the antinociceptive effects of oxycodone and the imidazoline I2 receptor agonist phenyzoline in adult male rats

Abstract: Rationale Emerging evidence suggests the potential utility of combining opioids with imidazoline I2 receptor agonists for chronic pain. However, chronic pain management requires prolonged pharmacotherapy and the consequence of such combination therapy remains unclear. Objective This study examined the anti-hyperalgesic effect of the opioid oxycodone, the selective I2 receptor agonist phenyzoline, alone and in combination, during prolonged treatment. Methods Von Frey filament test was used to examine the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…In a complete Freund’s adjuvant (CFA)-induced inflammatory pain model, three selective I 2 receptor ligands (2-BFI, BU224 and tracizoline) all dose-dependently and significantly reduced the mechanical and thermal hyperalgesia (Li, Thorn, Qiu, Peng, & Zhang, 2014). 2-BFI and the I 2 receptor ligand phenyzoline also reduced mechanical hyperalgesia in rats that received chronic constriction injury (CCI), a model of peripheral neuropathic pain (Li et al, 2014; Thorn, Zhang, & Li, 2017). The anti-hyperalgesic effect of 2-BFI was attenuated by idazoxan, confirming I 2 receptor mediated mechanism (Li et al, 2014).…”
Section: Neuropharmacology Of Imidazoline I2 Receptor Ligandsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a complete Freund’s adjuvant (CFA)-induced inflammatory pain model, three selective I 2 receptor ligands (2-BFI, BU224 and tracizoline) all dose-dependently and significantly reduced the mechanical and thermal hyperalgesia (Li, Thorn, Qiu, Peng, & Zhang, 2014). 2-BFI and the I 2 receptor ligand phenyzoline also reduced mechanical hyperalgesia in rats that received chronic constriction injury (CCI), a model of peripheral neuropathic pain (Li et al, 2014; Thorn, Zhang, & Li, 2017). The anti-hyperalgesic effect of 2-BFI was attenuated by idazoxan, confirming I 2 receptor mediated mechanism (Li et al, 2014).…”
Section: Neuropharmacology Of Imidazoline I2 Receptor Ligandsmentioning
confidence: 99%
“…However, doses higher than 20 mg/kg did develop antinociceptive tolerance after two weeks, a process that was substantially slower than that during buprenorphine treatment (Meregalli et al, 2012). We recently found that twice-daily treatment with phenyzoline at the dose that produced near maximal antinociceptive effect in the CFA and CCI rat chronic pain models for 19 days only produced a slight although significant antinociceptive tolerance (Thorn, Zhang, & Li, 2017). As a comparison, oxycodone produced dramatic tolerance to its antinociceptive effect under similar treatment conditions (Thorn, Zhang, & Li, 2017).…”
Section: Neuropharmacology Of Imidazoline I2 Receptor Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the dose-effect functions of isosakuranetin, the data at time 30-min post-injection were converted to percentage of maximal possible effect using the following formula: % maximal possible effect = (post-drug value for a behavioral response [g or s] - pre-drug value for a behavioral response/[presurgery baseline value - pre-drug value for a behavioral response] × 100). The ED 50 values and 95% confidence limits (CLs) of isosakuranetin in the different measures were determined by linear regression using the portion of the dose-effect curve spanning 50% as previously described [17]. For the rotarod test, data were analyzed with one-way ANOVA followed by post hoc Bonferroni test.…”
Section: Methodsmentioning
confidence: 99%